Laboratory Biosafety and Biosecurity - Upmanyu, Vikramaditya; Tiwari, Ashok K. (Indian Farming, 2015)
The Indian Veterinary Research Institute has been engaged inhandling pathogens of various risk groups since its establishment in 1889 with very good track record of maintaining adequate biosafety and biosecurity. The policies, procedures, actions and habits are generally adopted in the different laboratories of IVRI as per the standard guidelines. The efforts are still continued to improve present facilities and practices of biosafety and biosecurity as per GLP and GMP compliance, to prevent leakage/ spread of the pathogen.